Motor control electronics handbook - Valentine, Richard (McGraw-Hill handbooks, 1998)
This is a clear, up-to-the-minute guide to controlling all types of motors-with precise, adaptable intelligence. Featuring the latest in electronics technology, this expert-written guide gives you everything from the fundamentals to cutting-edge design tips, including real-life examples with software code. With this insider's guide to electronic control technology, you'll be ready to make motors work better now and into the future.